Russia's Regions : Income Volatility, Labor Mobility and Fiscal Policy - Kwon, Goohoon (IMF Working Papers; Working Paper, 2005)
Russia's regions are heavily exposed to regional income shocks because of an uneven distribution of natural resources and a Soviet legacy of heavily skewed regional specialization. Also, Russia has a limited mobility of labor and lacks fiscal instruments to deal with regional shocks. We assess how these features influence the magnitude and persistence of regional income shocks, through a panel vector autoregression, drawing on extensive and unique regional data covering last decade. We find that labor mobility associated with regional shocks is far lower than in the United States yet higher than in the EU-15, and that regional expenditures tend to expand in booms and contract in recessions. We discuss institutional factors behind these outcomes and policy implications.